Effective energy applied to a glass plate during an impact test. (August 2019) - Parra, J.A.; Alonso, J.; Pacios, A.; Huerta, M.C.
Highlights: Energy applied to a glass plate upon impact is 80% more than expected by drop height. Dynamic tests and 2DoF models used to predict impact energy dissipation with a difference of 4%. Impulse used to characterise the impact as in blast loads. An accelerometer necessary to measure the impact by impulse rather than drop height. Abstract: The study of the behaviour of glass plates under dynamic loads presents difficulties due to the uncertainty of the definition of load level, particularly in the case of human impact. The main differences from other impact tests are the dimensions of the specimens and the support structures for the various configurations, especially when tests are performed on a specific part of the building, for example, the facade. Even in tests performed under controlled conditions, in accordance with the standards, it can be observed that the level of excitation of the glass plate is clearly lower than expected if the initial height of the impactor is used. This has been observed in a test campaign involving 240 impacts, undertaken in accordance with EN 12, 600. The analysis of the data shows that a percentage of energy (20%) does not deform the glass and is distributed among the remaining parts of the configuration. An experimental model has been developed in regard to the energy dissipation in order to obtain a more realistic level of excitation of the plate, using the effective impulse obtained from an accelerometer located on the pendulum head.